"A better person coming out than going in": Community College Transfer Students and Constructivist Grounded Theory. Issue 6 (3rd June 2019) - Rodriguez, Sheri K.; Kerrigan, Monica Reid
ABSTRACT: This study explored community college transfer student (CCTS) identity, development, and engagement at four-year institutions. The grounded theory approach was applied to develop CCTS-specific theories. Relational maps and interview questions were included in the research design to explore meaning making given the intersections of identity, development, and engagement. Findings revealed three interlocking concepts, the mechanisms that CCTSs use to cope unanticipated conflicts they experience upon transitioning to their four-year institutions, leading to the desire for self-improvement. Implications for policy, practice, and research in addition to the study's limitations are also discussed.